CONTRIBUTION OF OFFLINE AND ONLINE TRAVEL AGENT RESERVATION TO ROOM REVENUE IN ALILA VILLAS ULUWATU - Made Indah Wulansari Pendit; Nyoman Mastiani Nadra; I Made Sudiarta (Journal of Applied Sciences in Travel and Hospitality, 2018)
This study enlightens the contribution of offline travel agent and online travel agent reservation to the room revenue at Alila Villas Uluwatu. The purpose of this research is to determine the contribution of offline travel agent and online travel agent reservation to the room revenue. Data collection technique used were observation, interview, and documentation study. The analysis technique used is statistic descriptive that are supported by qualitative analysis. The result of the research shows that the contribution of offline travel agent and online travel agent reservation for three years has fluctuated. The average contribution of offline travel agent reservations in 2015-2017 is 67.38%. In 2015 the average contribution was 77%, contributing 58% in 2016 and in 2017 the contribution of offline travel agents increased by contributing 66%, while the average contribution of online travel agent reservations in 2015- 2017 is 32.62%. In 2015 contributes 34%, in 2016 contributing an average of 42%, and in 2017 contributing 34%. There are 5 highest reservation contributions sourced from offline travel agents such as Jason Travel Korea, TMS Tour, Bali Kami, Airtours, and Windy's Bali Tour. In addition there are 5 highest reservation contributions sourced from online travel agents such as Booking.com, Agoda, Expedia, Hotelbeds, and Ctrip. The biggest contribution during 2015-2017 is sourced from offline travel agent.